Penampilan Pramusaji Dan Citra Restoran Di Kabupaten Bogor (Cisarua – Cipayung) - Mustika, Amalia; Achmadi, Mochammad; Desafitri, Linda (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2017)
This study aims to determine whether the grooming standards affect the image of the restaurant. The study conducted in the scope of the Regional of Bogor. This research used descriptive method correlation and unit of analysis of this research was employees of restaurant in Cisarua and Cipayung, with number of respondents was 32 persons. The results of the study have shown that the grooming of waiter variable significantly influence the image of restoran with 0.584, it meant between grooming of waiter and the image of restoran had a sufficient or moderate relationship. the grooming of waiter could explain the influence in the image of the restoran at regional of Bogor for 34.11%. and the balance 65.89% is explained by other variables which did not included in the this research.